RESPONS PERTUMBUHAN DAN PRODUKSI KEDELAI (Glycine max (L.) Merrill) YANG DIBERI FUNGI MIKORIZA ARBUSKULAR (FMA) PADA TANAH SALIN - Teguh Hakiki Nasution; Rosmayati Rosmayati; Yusuf Husni (Jurnal Agroekoteknologi, 2013)
Soybean crop productivity on saline land affected by the input that is given to the provisionof mycorrhizal plants. For which a research field trials have been conducted in the village ofTanjung Rejo District Percut Sei Tuan Deli Serdang regency (± 1.5 m asl.) In May-July 2012.Experimental was conducted using a factorial randomized block design that is mycorrhizalwith standard treatment (M0 = No provision of mycorrhizal and mycorrhizal granting M2 =10 g / plant), the treatment was repeated six times. The data were analyzed using variance(ANOVA) and continued with HSD.The analysis of data showed that administration ofmycorrhizae improve plant height at age 5 MST, the number of branches, number of podsand cropping, as well as accelerate the age of flowering plants.Key words: salinity, mycorrhizal